Effect of Increasing Malpractice Insurance Cost and Subsequent Practice of Defensive Medicine on Out-of-Hospital Birth Rates in the United States - Kim, Edward Kangsuhp; Fletcher, William James; Johnson, Clark Timothy (American Journal of Perinatology, 2019)
Background Across the United States, the burden of malpractice litigation has influenced obstetricians and obstetric institutions to avoid high-risk patients, favor cesarean delivery, and decrease availability of trial of labor after cesarean. Recently, the United States has experienced an increase in out-of-hospital (OOH) births.Objective The main purpose of this article is to investigate the association between malpractice insurance premium (MIP) and OOH births in the United States from 2000 to 2014.Study Design We analyzed changes in OOH birth rates and MIP from 2000 to 2014 using birth data from the National Vital Statistics System and Medical Liability Monitor's annual survey, respectively. The change in OOH birth rates was then compared with the change in MIP.Results Between 2000 and 2014, there has been approximately 60% increase in MIP from national average of $40,949 to $65,210 (p < 0.05). OOH births increased 57% from 39,398 births to 59,674 births (p < 0.05). There was a significant positive correlation between increase in MIP and increase in OOH births (p < 0.05, R2 = 0.14).Conclusion MIP and OOH birth rates have a significantly associated increase from 2000 to 2014. Given that malpractice climate affects other aspects of obstetric practice, we cautiously propose that increasing MIP may be associated with an increase in OOH births.
Keywords: malpractice; out-of-hospital birth; defensive medicine; United States; litigation